TEACHING NARRATIVE WRITING BY USING ROUNDTABLE STRATEGY TO ISLAMIC JUNIOR HIGH SCHOOL STUDENTS - Muammar Khadapi (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The objectives of this study were to find out whether or not (1) there was a significant improvement on the eighth grade students’ writing achievement between those who were taught by using roundtable strategy, and (2) there was a significant difference on the eighth grade students’ writing achievement between those who were taught by using Roundtable strategy. The population of this study consisted of 147 students. In this study, quasi experimental design, especially pretest-posttest non-equivalent groups design was used. The instrument used in collecting the data was writing test. The result showed that (1) there was a significant improvement from students’ pretest to posttest scores in experimental group taught by using Roundtable strategy since the p-output (0.000) was lower than 0.05 and t-obtained is higher than t-table df=31 (2.042) and (2) there was a significant difference from students’ posttest scores in control and experimental groups, since p-output (0.000) was lower than (0.05) and t-obtained is higher than t-table (df 62 = 2.000). So, the Ho (the null hypothesis) was rejected and Ha (the alternative hypothesis) was accepted. It means that there was significant difference on students’ narrative writing achievement taught using Roundtable than those who are not.